Saint Patrick’s Cathedral dari Sudut Pandang Konsep Perancangan - Albertus Prawata (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The Catholic diocese of Parramatta is well-known as the first established Catholic Church in Australia. It is the most recently completed Cathedral in Australia, designed by Romaldo Giurgola. As a foreigner, he was successfully applied the historical values and symbols of Catholic tradition shown on the design’s elements and forms throughout the Cathedral. This paper explores the design of the Cathedral Church of the Catholic diocese of Parramatta which is influenced by works of other architects such as Utzon and Van Eyck. The use of natural light and different materials’ quality in the interior and exterior of building are few of the design’s elements applied in the Saint Patrick Cathedral.